2009
DOI: 10.1007/s11746-009-1394-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of High Oleic Palm Oils on a Pilot Scale

Abstract: Refined, bleached and deodorized palm olein (RBD POo) with an iodine value (IV) of 62 was chemically interesterified with methyl oleate (MO) at a ratio of 50:50 (w/w). The reaction was carried out at 110°C in the presence of sodium methoxide as a catalyst using a 100-kg pilot scale reactor. Randomization between 15 and 30 min resulted in less free fatty acid (FFA) formation and higher oleic content in the interesterified product as compared to longer reaction time of 60-90 min. Sodium methoxidecatalyzed ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The acid value of POo and OA was 0.56% and increased to 8.09% and 67.32% after conversion to EPOo and diol, respectively. The iodine value of POo and OA were 61.47 mg KOH/g oil and 83.91 mg KOH/g oil which is almost similar to the work reported by Ramli et al [32] at 61.67 mg KOH/g oil and Derawi et al [8,14] at 62 mg KOH/ g oil, but slightly higher to the work reported by Ramli et al [33] at 78.2 mg KOH/g oil for the IV value of high-oleic acid palm oil. The POo was found to have a complete epoxidization to EPOo based on the reduction of the iodine value of POo from 61.47 to 0 mg KOH/g oil (Table 1), which corresponds to the complete conversion of the POo carbon double bond (C=C) to the epoxide (oxirane) ring of EPOo and similar to the reported previous study by Derawi et al at IV 61.67 drops to 3.30 to 0.51 [14].…”
Section: Differential Scanning Calorimetrysupporting
confidence: 89%
“…The acid value of POo and OA was 0.56% and increased to 8.09% and 67.32% after conversion to EPOo and diol, respectively. The iodine value of POo and OA were 61.47 mg KOH/g oil and 83.91 mg KOH/g oil which is almost similar to the work reported by Ramli et al [32] at 61.67 mg KOH/g oil and Derawi et al [8,14] at 62 mg KOH/ g oil, but slightly higher to the work reported by Ramli et al [33] at 78.2 mg KOH/g oil for the IV value of high-oleic acid palm oil. The POo was found to have a complete epoxidization to EPOo based on the reduction of the iodine value of POo from 61.47 to 0 mg KOH/g oil (Table 1), which corresponds to the complete conversion of the POo carbon double bond (C=C) to the epoxide (oxirane) ring of EPOo and similar to the reported previous study by Derawi et al at IV 61.67 drops to 3.30 to 0.51 [14].…”
Section: Differential Scanning Calorimetrysupporting
confidence: 89%
“…They happily report measurements that a critical examination should have discarded as most unlikely and/or caused to be repeated. I recently sent a Letter to the Editor of the JAOCS pointing out that one of its articles [62] proved the existence of God by reporting that something had been created out of nothing. I continued my letter by explaining how analytical mistakes were responsible for this 'proof ' and concluded that the article should never have been published.…”
Section: Discussionmentioning
confidence: 99%
“…So if in a sample the polyunsaturated fatty acid content decreases by oxidation, its saturated fatty acid content is automatically increased to maintain a sum of 100% despite the fact that some material does not elute. I also mentioned an article (Ramli et al, 2009) about the production of a low cloud point palm olein I had also commented upon in my recent review (Dijkstra, 2009b); since this comment has been submitted as a Letter to the Editor of the Journal of the American Oil Chemists' Society (in press) I will not discuss it here. On the other hand, there is an article (Holm and Cowan, 2008) that I did not mention during my presentation but discussed in my review (Dijkstra, 2009b) as an example of an otherwise excellent article that sadly enough was biased and even misleading for commercial reasons.…”
Section: Secondary Nucleationmentioning
confidence: 99%